2015
DOI: 10.1016/j.drugalcdep.2014.09.373
|View full text |Cite
|
Sign up to set email alerts
|

Opioid substitution therapy as a strategy to reduce deaths in prison: Retrospective cohort study

Abstract: Objectives: To describe deaths in prison among opioid-dependent people, and examine associations between receipt of opioid substitution therapy (OST) and risk of death in prison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Bird & Hutchinson found that males aged 15-35 years had a DRD risk seven times (95% CI = 3. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] higher in the first than per 2 weeks in the subsequent 10 weeks [2]. Further, 60% of DRDs within 12 weeks of release had occurred within the first 2 weeks.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bird & Hutchinson found that males aged 15-35 years had a DRD risk seven times (95% CI = 3. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] higher in the first than per 2 weeks in the subsequent 10 weeks [2]. Further, 60% of DRDs within 12 weeks of release had occurred within the first 2 weeks.…”
Section: Introductionmentioning
confidence: 96%
“…Opiate substitution therapy (OST) aims to reduce the use of illegal and injected opiates by providing safer substitutes such as oral methadone. Provision of OST in prisons, besides being good clinical practice, seems to have contributed to a reduction of in-prison deaths [11], including suicides by younger inmates [12] and of injecting while in prison, with its attendant risks of blood-borne virus transmission [13][14][15][16][17]. Another possible benefit of prison-based OST might be to prevent the loss of opiate tolerance and so reduce the risk of DRD after release.…”
Section: Introductionmentioning
confidence: 99%
“…Further changes to grant exemptions for trained peer workers to supply naloxone, as is common practice in Scotland (through the established naloxone peer education initiative [24]), are important avenues to explore. In addition, the provision of opioid substitution treatment combined with pre-release/postrelease programs with naloxone may help to address the high level of opioid-related mortality that has been observed following release from incarceration [25].…”
Section: Futurementioning
confidence: 99%
“…This treatment is potentially lifesaving not only prior to release but also during incarceration. Among incarcerated people, the hazard of all-cause in-prison death during the first four weeks of incarceration was 94 percent lower while on opioid agonist therapy than while not on it [20].…”
Section: Clinical Evidence Base For Opioid Agonist Therapymentioning
confidence: 99%